Travelers’, migrants’ and refugees’ health – individual, population and systemic aspects - Cianciara, Dorota; Pruszyński, Jacek; Włodarczyk-Pruszyńska, Inga; Padzińska-Pruszyńska, Irena; Szmigiel, Andrzej (Journal of Education, Health and Sport, 2023)
Introduction Mobility, the ability to move from the place of residence, is a sign of the times. It results from many grounds and conditions. Numerous groups of mobile people can be distinguished. Changing the place of residence poses a health risk for mobile persons and, in the case of infectious diseases, also for people who may be in contact with them. Two groups of mobile people are in focus of the public health: the travelers and migrants and refugees. Purpose A panoramic presentation of selected issues related to multifacets and complex problem of travelers and migrants, health. Health risks and health interventions related to travel and migration are discussed, as well as system solutions for the health of travellers, migrants and refugees. State of knowledge Departures of travelers are induced by intrapersonal factors. The health risk depends on the state of health, the travel/transport conditions and mode, the specificity of the destination and the behavior of the traveller. Risk factors are relatively well recognized, including those of a biological nature. Health interventions have a long tradition, there are rules for systemic actions, but improvement of existing solutions is expected. Departures of migrants and refugees are caused by external factors. Health risk is multidimensional and related to the migration phase (pre-migration, movement, arrival). Risk factors for the health of migrants are insufficiently recognized and can be of a very diverse nature - physical, chemical, biological, psychophysical and social. Health interventions are poorly established and focused on improving access to healthcare. The necessity for a broader spectrum of activities, including political, interdisciplinary, multisectoral and global ones is pointed. Summary Travelers’, migrants’ and refugees’ health are becoming increasingly important nationally and internationally.